On the applicability theory to differential operators of infinite order in spaces of functions of several variables - Morzhakov, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. В. Моржаков. К теории применимости дифференциальных операторов бесконечного порядка в пространствах функций нескольких комплексных переменныхV. Moržakovas. Begalinės eilės diferencialinių operatorių daugelio kintamųjų funkcijų erdvėse pritaikomumo klausimu